2004
DOI: 10.1021/ja047190o
|View full text |Cite
|
Sign up to set email alerts
|

Formal Total Synthesis of Oximidine II via a Suzuki-Type Cross-Coupling Macrocyclization Employing Potassium Organotrifluoroborates

Abstract: A formal total synthesis of oximidine II has been achieved, employing a Suzuki-type coupling approach to construct the highly strained, polyunsaturated 12-membered macrolactone. To achieve this goal, benefit was derived from the stability of potassium alkenyltrifluoroborates to establish conditions for the macrocyclization. The stereocontrolled formation of the cis-1,2-diol subunit was accomplished using a diastereoselective, reagent controlled addition to a chiral aldehyde utilizing the Carreira protocol. Adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(65 citation statements)
references
References 64 publications
1
63
0
1
Order By: Relevance
“…After the mixture had been continuously stirred for 6 h at room temperature, it was diluted with water and extracted with Et 2 O. The organic layer was washed with brine and dried over MgSO 4 , and the solvent was evaporated to leave a residue, which was purified by chromatography on silica gel to afford the corresponding aldehyde (2.18 g, 92 %) as a pale-yellow oil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the mixture had been continuously stirred for 6 h at room temperature, it was diluted with water and extracted with Et 2 O. The organic layer was washed with brine and dried over MgSO 4 , and the solvent was evaporated to leave a residue, which was purified by chromatography on silica gel to afford the corresponding aldehyde (2.18 g, 92 %) as a pale-yellow oil.…”
Section: Resultsmentioning
confidence: 99%
“…After the mixture had been stirred for 30 min at room temperature, the aldehyde (2.18 g, 6.92 mmol) in THF was added and the resulting mixture was stirred for 10 h. The reaction mixture was diluted with saturated NH 4 Cl and the aqueous mixture was extracted with Et 2 O. The organic layer was dried over MgSO 4 and then evaporated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenyl substituted halo dienes (43)(44)(45) were directly generated from the corresponding allenic alcohol (41) using the established protocol of Ma et al 49 We found that the temperature of the rearrangement reaction has significant impact on the product yield for the formation of the iodo-substituted diene (43). In the presence of 1.5 mol% Pd catalyst the reaction could be performed at 40°C for both the bromo-and chloro-substituted dienes (44,45). 50 Attempts to run the rearrangement reaction at temperatures even 10 o C higher than this for the iodo-substituted diene (43) resulted in product yields of <10% yield.…”
Section: Preparation Of 4-aryl-2-boron Substituted 13-butadiene and mentioning
confidence: 99%
“…Newly formed halo-dienes (43)(44)(45) were first subjected to the protocol (used for formation of the unsubstituted 2-BF 3 diene (27)) to attempt to prepare the corresponding BF 3 -substituted dienes. The first step was to generate the corresponding Grignard reagent followed by addition of trimethoxy borate and quenching by KHF 2 /H 2 O.…”
Section: Initial Attempts To Make 4-substituted 13 Dienyl-2-trifluormentioning
confidence: 99%